Design and implementation of energy efficient reconfigurable networks (WORN-DEAR) for BAN in IOT environment (BIOT). (2018) - Kumaresan, P.; Prabukumar, Manoharan
Embedded systems are pervasive with the advent of internet of things. This has led smart devices to be omnipotent. Even though the technology becomes omnipotent, several research problems arise in design and implementation. Here, we have concentrated on the low power healthcare system based on body area networks (BAN) in which the technology embeds the body area networks with internet of things (IOT) which can be jointly coined as BAN internet of things (BIOT). BIOT finds application as wearable devices for monitoring and care giving systems for patients. Due to BIOTs nature of omnipotent application in the healthcare, maintaining its life time remains in the darker side of the research. To overcome this problem, a new algorithm for the BIOT called wake-on reconfigurable networks (WORN) has been proposed. The proposed algorithm works on the distance energy adaptive rule (DEAR) rule sets. By increasing the life time of the devices, BIOT with WORN-DEAR power model will be the bridge between the human and the machine interface.